Synthesis and Antibacterial Activity of N9-(Phenylidenehydrazidomethyl)carbazoles - Valarmathi, R.; Akil, S.; Karpagam Kumara Sundari, S.; Panneerselvam, P. (Asian Journal of Chemistry, 2010)
N9-(Phenylidenehydrazidomethyl)carbazole derivatives are synthesized by condensing various aromatic aldehydes. These are characterized on the basis of IR, NMR and mass spectral data. The final compounds were evaluated for antibacterial activity by taking Staphylococcus aureus as test organism.